VD_FINDINFO Décision / 2012 / 675 vom 13. August 2012 - VD Tribunal cantonal (2012)
SUSPENSION DE LA PROCÉDURE, ADMINISTRATION DES PREUVES, LÉGALITÉ, EXPERTISE | 141 CPP (CH), 184 CPP (CH), 314 al. 1 let. b CPP (CH)